2006
DOI: 10.1080/08989620600848561
|View full text |Cite
|
Sign up to set email alerts
|

Deception in Psychology: Moral Costs and Benefits of Unsought Self-Knowledge

Abstract: Is it ethically permissible to use deception in psychological experiments? We argue that, provided some requirements are satisfied, it is possible to use deceptive methods without producing significant harm to research participants and without any significant violation of their autonomy. We also argue that methodological deception is at least at the moment the only effective means by which one can acquire morally significant information about certain behavioral tendencies. Individuals in general, and research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 12 publications
0
36
0
Order By: Relevance
“…Johansson, Hall, Sikström, and Olsson (2005), for example, used sleight of hand to substitute photographs that participants chose as more attractive with those that they deemed less attractive; this paradigm demonstrated the robustness of the choice blindness effect, with participants often failing to notice the substitution. Conjuring, moreover, may provide new leads for the use of deception-a common, albeit ethically tenuous, methodology (Bortolotti & Mameli, 2006;Clarke, 1999;Pascual-Leone, Singh, & Scoboria, 2010;Sharpe, 1992). Magic may allow the experimenter to effectively mislead the participant without lying (Lamont, et al, 2010)-an attractive way to apply deception in research.…”
Section: Discussionmentioning
confidence: 99%
“…Johansson, Hall, Sikström, and Olsson (2005), for example, used sleight of hand to substitute photographs that participants chose as more attractive with those that they deemed less attractive; this paradigm demonstrated the robustness of the choice blindness effect, with participants often failing to notice the substitution. Conjuring, moreover, may provide new leads for the use of deception-a common, albeit ethically tenuous, methodology (Bortolotti & Mameli, 2006;Clarke, 1999;Pascual-Leone, Singh, & Scoboria, 2010;Sharpe, 1992). Magic may allow the experimenter to effectively mislead the participant without lying (Lamont, et al, 2010)-an attractive way to apply deception in research.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] On the other hand, deception has been justified on the basis that it increases methodological control and the likelihood of capturing spontaneous responses to experimental manipulation, thus often resulting in valuable scientific discovery. 3,13 When deception studies are carefully designed to avoid or minimize harm, pose no greater than minimal risk to participants, and when it is otherwise impossible/impractical to answer the research question, its use has been deemed to be ethically appropriate and justified by national regulatory bodies. However, the research should not involve a therapeutic, clinical, or diagnostic intervention, and adequate debriefing is crucial.…”
Section: The Acceptability Of Deception In Pediatric Researchmentioning
confidence: 99%
“…Parents and children separately rated the majority of probed recall questions on 0 to 10 numerical rating scales. The language and phrasing of the questions and anchors were designed to be developmentally appropriate for parents as well as children aged [10][11][12][13][14] years.…”
Section: Deception Impact Study Interviewmentioning
confidence: 99%
“…Christensen also suggests that it is more unethical to refuse to do research on important social problems because of unrealistic repugnance over the notion of deceiving subjects. Bortolotti and Mameli (2006) similarly argue for the value of deception in research, suggesting that . .…”
mentioning
confidence: 99%
“…First, psychologists largely embrace the use of deception while economists eschew it. Experiments published in high-impact social psychology journals commonly use deception (Bortolotti and Mameli 2006;Christensen 1988), which is understood to represent an effective means of eliciting truthful beliefs and behaviors from subjects who will be less able to consciously affect their behavior to manage their impressions or to please the experimenter. Christensen (1988) argues that "research has revealed that subjects who have participated in deception experiments versus nondeception experiments enjoyed the experience more, received more educational benefit from it, and did not mind being deceived or having their privacy invaded.…”
mentioning
confidence: 99%